Chronic obstructive pulmonary disease in organized groups - G. T. Tаshmetovа; I. V. Liverko (Туберкулез и болезни лёгких)
The objective: to study the prevalence of chronic obstructive pulmonary disease (COPD) in adult organized groups, to assess the structure and risk factors of its development.Subjects and methods. 3,000 people of the organized population working at various enterprises in Tashkent aged 20 to 60 years (1,400 (46.7%) women and 1,600 (53.3%) men) underwent the contemporary pulmonological screening.Results. The active pulmonological screening aimed to detect COPD among organized groups has been justified; examination of 3,000 people allowed detecting 198 (6.6%) new patients additionally to 65 cases that were already known at the time of screening. The chances of developing COPD increase with the presence of risk factors such as smoking, exposure to toxic substances and chemicals, and recurrent upper respiratory tract infections.